Political change in South East Asia - Bertrand, Jacques, 1965- (Cambridge : Cambridge University Press, 2013)
'Southeast Asia is a vast and complex region, comprised of countries with remarkably diverse histories and cultures. Jacques Bertrand provides a fresh and highly original survey of politics and political change in this area of the world. Against the backdrop of rapid economic development and social transformation in several Southeast Asian countries, he explores why some of these countries have adopted democratic institutions, while others have maintained stable authoritarian systems or accepted communist regimes. Bertrand presents a historically grounded account of capitalist countries and state-socialist countries, delving into the historical experience of individual countries, while simultaneously providing a comparative framework with which to draw parallels and foster a better understanding of the political and economic dynamics both within and between the countries'--
Understanding political change in Southeast Asia -- Part I. Capitalism, economic growth and political change -- Indonesia and Timor-Leste -- The Philippines -- Malaysia and Singapore -- Thailand -- Part II. State-socialist countries and authoritarian stability -- Vietnam -- Cambodia and Laos -- Burma/Myanmar -- Southeast Asia in the twenty-first century.
Includes bibliographical references (pages 229-236) and index.
Keywords: Southeast Asia -- Politics and government -- 20th century; Southeast Asia -- Politics and government -- 21st century